The Effect of Short Term Alcohol Abstinence on Neutrophil Phagocytic Properties (International Journal of Physiology, 2021)
Background : Alcohol dysregulates the innate immunity in numerous ways, making alcohol dependantsmore susceptible to varied forms of infections and immunological assaults.Objective : The current study on alcoholics throws light on the consequence of short term alcohol abstinenceon neutrophil phagocytic power.Method : 21 subjects meeting the inclusion and exclusion criteria were enrolled for the study.Their bloodsamples were collected before and after a period of abstinence and studied for neutrophil phagocytic indexusing Candida phagocytic assay test.Result : An increase in the Mean Particle Number(MPN) of phagocytosis was observed in all the individualsafter the alcohol-free period.Conclusion : The improvement in phagocytic ability of neutrophils post-abstinence provides us an insightinto the ways alcohol manipulates the defense mechanism of the human body .Understanding this might helpus in exploring novel ideas to circumvent the mortality and morbidity in alcoholics.